BENTHIC ECOSYSTEM VARIATIONS ALONG THE MIDDLE EOCENE PROVENÇAL DROWNING RAMP (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
High-resolution lithology, fossil content, ichnofabrics, and spectral gamma-ray emissions are studied in the Capo Mortola section in the Liguria region (NW Italy), correlating it with other sections in the same area during the middle Eocene (Bartonian). The succession unconformably overlies Upper Cretaceous open-marine deposits and records a deepening trend on a carbonate ramp during the middle Eocene. Six different microfacies have been recognized along the section, recording the variation in fossil content, especially in the larger benthic foraminiferal assemblages, and the lithology, which indicate a deepening trend in the succession. The variation in Th/U ratios allows for differentiation of oxidizing, normal, and reducing conditions throughout the succession. The increase in the concentration of Th and K suggests periods of increased terrigenous material, which was supplied by a fluvial system close to the studied section. In turn, the Th/K ratio shows an alternation between smectite and kaolinite, which are respectively associated with warm-humid and seasonal humid/dry climates. The upper part of the section shows the incipient drowning of the ramp and differs from nearby studied sections in biotic components, lithology, and depth of the basin related to the specific paleogeographic settings of each portion of the ramp. We were able to identify sectors more prone to seafloor instabilities due to their proximity to the shoreline and the deltaic influence, whereas others were located considerably deeper or farther out with respect to the input of deltaic sediments.
Keywords: Bartonian; microfacies; trace fossils; larger benthic foraminifera; spectral gamma-ray; shallow water; paleoenvironment; Ligurian Alps.